Investigation of the Interaction of Monoamine Oxidase (MAO) Inhibitor Biscoumarins with Hemoglobin and Albumin Using Multi-Spectroscopic Techniques and Molecular Docking - MELETLİ, FURKAN; DANIŞ, ÖZKAN (My University, 2024)
Coumarin and their derivatives, such as biscoumarins, which are found as active ingredients in a variety of drugs, possess a wide range of biological activities. In this paper, the inhibitory effects of biscoumarin derivatives B1 and B2 on monoamine oxidase (MAO) enzyme activity were studied. Their binding mechanism to bovine serum hemoglobin (BHb) and bovine serum albumin (BSA) was investigated using molecular docking and multi-spectroscopic methods such as absorption, fluorescence, and synchronized fluorescence spectroscopy. The fluorescence quenching processes were analyzed using the Stern-Volmer, Lineweaver-Burk, and Hill methods. In this regard, Stern-Volmer quenching constants (Ksv), Lineweaver-Burk constants (KLB), and binding constants (Ka) were calculated at three temperatures (298, 310 and 322 K). The fluorescence studies showed that the binding of biscoumarins to BHb or BSA was a driven by static quenching. The Ka values of B2 to BHb and BSA (2179.11 and 18453.98 x 105 M-1) was larger than B1 at corresponding temperature (62.75 and 599.90 x105 M-1 for BHb and BSA, respectively), which indicates that the affinity of B2 toward the proteins were higher than that of B1. Moreover, thermodynamic parameters explained that hydrogen bonds were the main binding force stabilizing the protein-ligand complexes. Additionally, molecular docking studies have revealed binding energies, ligand efficiency values, and interactions with amino acid residues of proteins. The results of these investigations may be helpful in analyzing drug-protein binding of biscoumarins for potential future applications.
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Fizikokimya; Elektrokimya; Spektroskopi; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Physical Chemistry; Electrochemistry; Spectroscopy; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Biyoloji ve Biyokimya; KİMYA, ANALİTİK; SPEKTROSKOPİ; ELEKTROKİMYA; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; ELECTROCHEMISTRY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Fizik Bilimleri; Klinik Biyokimya; Biyokimya (tıbbi); Physical Sciences; Clinical Biochemistry; Biochemistry (medical); Albumin; biscoumarin; hemoglobin; molecular docking; monoamine oxidase